Comparative analysis of physiologically important fatty acids - Kövér, Gabriella; Győri, Zoltán (Acta Agraria Debreceniensis, 2010)
Fatty acid composition of some vegetable oils, like wheat germ, walnut, peanut, hempseed, linseed, sunflower-seed, olive, rapeseed, grape seed or pumpkin seed, analysed at Food Science Institute of Debrecen University, are summarised here. The effect of heat treatments usually used in Hungarian cuisine was examined in this paper.The influence of different fatty acids on human health is also reviewed.